NILAI-NILAI PENDIDIKAN ISLAM DALAM SYAIR LAGU NASYID - Romli Romli (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
This article discusses about the Islamic Educational Values that can be enjoyed through the lyrics of Nasyid. The Islamic educational value here is meant as a set of belief which is accepted for its truthfulness and is aimed at developing Muslim characters physically and spiritually. Nasyid is a kind of Islamic music that can be utilized as a media to deliver Islamic teaching values through its lyrics. It can be understood because human likes art especially music. The values that can be aroused from the Islamic lyrics cover many things such as the value of faith, the value of worship to Allah and the value of moral which all derives from Al-Qur’an and Sunnah